Mechanical and structural performance of melt-processable bioresorbable engineering nanocomposites - Ward, Michael (2018)
The design of materials for medical implants is continuously evolving to improve their performance to address clinical needs. The development of a fully bioresorbable material with properties similar to bone is desirable for the replacement of existing metallic implants. This thesis forms part of a recent interdisciplinary effort to develop a scalable manufacturing route for the next generation of melt-processable bioresorbable polymer nanocomposites based on poly (lactic acid) (PLA) and nanohydroxyapatite (nHA). Recent progress in nanoparticle synthesis has enabled large scale production of nHA with different morphologies, forming either nanorods or nanoplatelets. The nanoplatelets can also be surface-modified during production, allowing for different surface coatings to be added to aid the dispersion process. PLA has been selected as the matrix material as it is already a popular choice for commercialised bioresorbable medical implants like small screws and pins. The focus of this work is on the structural and mechanical properties of melt-compounded nHA/PLA nanocomposites from the point of production through to the end of useful implant life, and on the understanding of the degradation mechanism of the PLA and the influence of the nHA on material performance. The accelerated hydrolytic response in phosphate buffer solution (PBS) of three commercial Evonik Resomer® PLA grades, LR 704s, LR 706s, and LR 708, was investigated. It was found that the presence of acidic chain ends in LR 708 increased the rate of hydrolysis relative to ester chain ends in LR 704s and LR 706s, and as a result induced autocatalysis much faster; autocatalysis was visible after 14 d for LR 708 and after 21 d for LR 706s. The presence of low molecular weight species within the distribution was also identified as a factor leading to faster degradation, and grade LR 706s was selected for compounding with nanoparticles. The rate of diffusion of water into PLA was measured in LR 706s and shown to obey Fickian diffusion with an activation energy of 48.6 ± 2.3 kJ mol-1. Creep compliance was measured in bending and was shown to plateau after one day of hydrolytic saturation, but increased again after 10 d due to autocatalysis leading to localised degradation. The use of a pH sensitive dye and microCT imaging provided further insight into the phenomenon. It was also shown that the rate of molecular weight loss increased by 20 times when raising the temperature of the degradation medium from 37 to 50 °C, increased due to the increased energy to break the ester bond alongside the increased autocatalysis due to the chain scission occurring at a much faster rate than diffusion of the breakdown products. Nanocomposites were produced by melt-compounding LR 706s with 2.5, 5 and 10 wt. % of uncoated nHA nanorods, nanoplates and dispersant-coated nanoplates. The presence of water during extrusion caused significant molecular weight loss to the polymer as a result of the increased energy that extrusion at 210 °C would provide to the water to enable hydrolysis of the ester bonds to occur. The molecular weight in the polymer was shown to fall from 422.4 kDa to (187.8 ± 18.0) kDa after extrusion in an air atmosphere. Nitrogen fed through a cold trap was used to prevent this. A pre-drying stage applied to the uncoated nanoparticles also helped to reduce degradation during the extrusion, and polymer processed with dried nHA retained a higher molecular weight (378.6 ± 11.4) kDa than a polymer without the pre-drying stage (327.7 ± 3.1) kDa. Dry nanorod-filled materials exhibited a modulus of up to (5.1 ± 0.2) GPa (at 10 wt. %) compared with (3.8 ± 0.5) GPa for the unfilled polymer, but only moderate increases in strength, from (106 ± 3) MPa to (108.1 ± 2.2) MPa (at 2.5 wt. %), were observed in the nanofilled materials. Both nanorods and nanoplatelets offered a degree of control over the rate of degradation, with a rate of change of molecular weight almost 2.5 times faster possible with 10 wt. % addition of particles. This could be helpful in tuning the implants to transfer loads back to the healing bones in shorter times. The strength of the nanocomposites during degradation was shown to correlate with the molecular weight, remaining constant at ca (44.9 ± 0.7) MPa until the molecular weight dropped to below 58 kDa, when it reduced approximately linearly with molecular weight. In conclusion, the addition of nHA compounded with suitable care offers unique opportunities for the design of materials with some increases in dry mechanical properties, and controllable degradation timescales.